2014
DOI: 10.1111/nhs.12147
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional investigation of depressive, anxiety, and stress symptoms and health‐behavior participation in Australian university students

Abstract: Transitioning to university involves a major life change that can have implications for physical and mental health. This study had three objectives: first, assess the mental health and health-behavior participation of Australian university students; second, evaluate clustering of health behaviors; and third, examine how mental health relates to health behaviors. University students (n = 751) enrolled at an Australian regional university completed an online survey containing the Depression, Anxiety, and Stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 34 publications
(78 reference statements)
6
78
4
3
Order By: Relevance
“…This means that the rest faced their daily activities sleepy and tired. This finding is the same as that reported in Australian nursing students (Lovell, Nash, Sharman, & Lane, ). In a research in the University of Huelva in Spain (Dominguez, Díaz, Rivera, & Rivera, ), it was found that 50% of the nursing students had a deteriorated sleep pattern.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the rest faced their daily activities sleepy and tired. This finding is the same as that reported in Australian nursing students (Lovell, Nash, Sharman, & Lane, ). In a research in the University of Huelva in Spain (Dominguez, Díaz, Rivera, & Rivera, ), it was found that 50% of the nursing students had a deteriorated sleep pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 4,333 middle-aged Japanese men suggested that depressive symptom were related to accumulation of visceral adipose, not subcutaneous adipose (Yamamoto et al, 2016). Potential mechanisms underlying these associations include hypothalamic-pituitary-adrenal axis (HPA-axis) dysregulation with hyper-cortisolemia (Yokoyama et al, 2015), inflammation (Miller et al, 2002), and the influences of lifestyle and behaviors (Lovell et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…found that the mild and higher levels of depression, anxiety, and stress among US college students were 29, 27, and 24%, respectively. In a sample of Australian students, rates of depression, anxiety, and stress were 21.8, 28.5, and 26.5%, respectively . In a sample of Canadian undergraduate nursing students, the rates of depression, anxiety, and stress were 33, 39, and 38%, respectively.…”
Section: Introductionmentioning
confidence: 91%